Measurement of the absolute branching fraction for D0→K-π+ - AKERIB, D.; et al. (Institutional Knowledge at Singapore Management University, 1993)
Using 1.79 fb−1 of data recorded by the CLEO II detector we have measured the absolute branching fraction for D0→K−π+. The angular correlation between the π+ emitted in the decay D*+→D0π+, and the jet direction in e+e−→cc¯ events, is used to determine the total number of inclusive D0 mesons produced from this source. The subsequent reconstruction of the decay chain D*+→D0π+,D0→K−π+ allows a measurement of the absolute D0→K−π+ branching fraction. Correcting for decay radiation in the final state, we find scrB(D0→K−π+)=[3.95±0.08(stat)±0.17(syst)]%.